1999
DOI: 10.1242/dev.126.6.1281
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a novel gene, Xin, in cardiac morphogenesis

Abstract: A novel gene, Xin, from chick (cXin) and mouse (mXin) embryonic hearts, may be required for cardiac morphogenesis and looping. Both cloned cDNAs have a single open reading frame, encoding proteins with 2,562 and 1,677 amino acids for cXin and mXin, respectively. The derived amino acid sequences share 46% similarity. The overall domain structures of the predicted cXin and mXin proteins, including proline-rich regions, 16 amino acid repeats, DNA-binding domains, SH3-binding motifs and nuclear localization signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Supervillin and Xin are important for organization of actin in cells, which fits nicely in the hypothesis that during stage HH30/31 and later stages massive muscle development takes place. Ankyrin3 is important for normal electrical activity in cardiomyocytes and ankyrins are essential for the development of excitable membrane domains in heart tissue .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Supervillin and Xin are important for organization of actin in cells, which fits nicely in the hypothesis that during stage HH30/31 and later stages massive muscle development takes place. Ankyrin3 is important for normal electrical activity in cardiomyocytes and ankyrins are essential for the development of excitable membrane domains in heart tissue .…”
Section: Discussionsupporting
confidence: 85%
“…Desmoplakin is important for cellular organization by stabilizing desmosomes and its presence is fundamental for proper development of the embryonic heart. 17 Literature confirms the expression of xin 14 and titin/connectin 18 in the chicken embryonic heart. In the present study, we show that these proteins differentiate among stages and tissues investigated.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A possible experimental approach may be co-culture of muscle cells with motor neurons in a 3D cell culture. 1,28,[66][67][68] Target-like fibres that might develop in this setting could then be examined with a multitude of techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, its localization at adherens junctions of muscle cells and interaction with β-catenin, filaminC, and Mena/VASP imply a role in linking and transducing signals important for cardiac remodeling. Inactivation of Xin in chick embryos led to looping defects, abnormal beating behavior and edema (Wang et al, 1999), while Xin-deficient mice display myopathy, impaired contractility, and attenuated muscle repair (Al-Sajee et al, 2015), which indicating a crucial role in heart development and cardiac disease. Moreover, it has been observed that Xin may participate in a BMP-Nkx2.5-MEF2C pathway and promote the expression of ventricular myosin heavy chain (vMHC) gene to participate in cardiogenesis regulation (Wang et al, 1999(Wang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%